A descriptive study on the accuracy of the diagnosis of UPCD clinicians - Bermejo, Libertine S.; Latido, Lovella P.; Yumul, Giselle (Adviser).
The study was conducted to assess the efficiency of the diagnosis of University of the Philippines College of Dentistry clinicians. The proponents intended to find out the perceptions of senior clinicians about the factors that may contribute to the efficiency of the diagnosis. Using a descriptive research design, the study provides a picture of the clinical set-up at the University of the Philippines College of Dentistry clinics involving clinician's attitude towards work, efficiency of faculty supervision, working environment and time. Questionnaires were distributed to all Clinical 40 students with a total of 50 students coming from the various sections which include Operative Dentistry Section, Oral Medicine Section and Prosthodontic Section. Grades in diagnosis were collected to assess the quality of clinicians' performance in diagnosis. The mean grades and standard deviation were computed to represent this. Among the 50 clinicians, it was discovered that every section has areas that require improvement to promote better performance in diagnosis. Results reveal that the mean grade of clinicians of Clinical 40 is 4. Therefore, clinicians' performance in diagnosis is above average but can become optimal if given better clinical set-up.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Students, Dental -- University of the Philippines